Strengthening the Values of Dandangan Tradition among Youth in Kudus Regency Based on Local Wisdom - Kholiq, Jamaludin Abdul; Prajanti, Sucihatiningsih Dian Wisika; Priyanto, Agustinus Sugeng (JESS (Journal of Educational Social Studies), 2025)
Globalization and modernization impact the shifting lifestyle of the youth, moving them further away from local wisdom values. This research aims to analyze the local wisdom values contained in the Dandangan Tradition in Kudus Regency, analyze how the youth in Kudus Regency interpret the Dandangan Tradition, and analyze the implementation strategies for strengthening the values of the Dandangan Tradition among the youth in Kudus Regency. This research applies a qualitative method with a descriptive approach. Data were collected through observation, interviews, and document review. To ensure the validity of the data, source triangulation techniques were used, while the data analysis process included stages of collection, reduction, presentation, and conclusion drawing. The research findings reveal that: 1) The Dandangan tradition contains various local wisdom values, which include religious, cultural, economic, and social values. 2) The youth in Kudus Regency interpret the Dandangan Tradition as seeking blessings from Sunan Kudus, an opportunity to earn income, and entertainment. 3) The strategy for implementing the strengthening of Dandangan Tradition values among the youth in Kudus Regency includes introducing it from childhood, social media, and holding night markets. This research is beneficial as a guide for the preservation of local culture by the youth.